2015
DOI: 10.1155/2015/353202
|View full text |Cite
|
Sign up to set email alerts
|

Lung and Nodal Involvement in Nontuberculous Mycobacterial Disease: PET/CT Role

Abstract: Introduction. Systematic use of 18F-FDG PET/CT has the potential to simultaneously assess both pulmonary and lymph node involvement in nontuberculous mycobacterial (NTM) lung infection. Objective. The aim of the study was to evaluate the role of 18F-FDG PET/CT in the assessment of both mediastinal lymph nodes and lung involvement in NTM patients compared with active tuberculosis (TB) patients. Methods. 26 patients with pulmonary NTM disease were selected; six consecutive patients had undergone 18F-FDG PET/CT a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 17 publications
1
15
0
Order By: Relevance
“…Conversely, other authors [37] demonstrated average values of lung lesions were less in NTM than in tuberculosis.…”
Section: Acute Infectious Processesmentioning
confidence: 75%
“…Conversely, other authors [37] demonstrated average values of lung lesions were less in NTM than in tuberculosis.…”
Section: Acute Infectious Processesmentioning
confidence: 75%
“…In MAC infection, macrophages are activated and play an important role in the formation of granulomas which increases the FDG uptake, and consequently, PET-CT scans show enhanced FDG uptake in patients with MAC infection. The average SUV max for LNs in NTM infection is 3.59 ± 2.32 (range 1.14 - 9.01), while for TB infection, this value is 7.23 ± 3.03 (range 1.78- 15.72) [17]. Based on our patient's abdomen/pelvic CT and PET-CT finding, we suspected a lymphoma and conducted a LN biopsy that revealed LN involvement of MAC.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, subspecies identification is becoming increasingly important for NTM therapy. 18 Giudice et al 19 reported that PET-CT has the potential to identify both pulmonary and lymph node NTM infection and showed an average SUV of 1.21 AE 0.29 (range: 0.90-1.70) in affected mediastinal lymph nodes. In the present case, PET-CT showed a maximum SUV of 10.2 in bilateral cervical lymph nodes.…”
Section: Discussionmentioning
confidence: 99%